2015
DOI: 10.1111/his.12878
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological features of endometrial carcinomas associated with POLE mutations: implications for decisions about adjuvant therapy

Abstract: Aims To characterize the histomorphological features of endometrial carcinomas (ECs) harbouring polymerase ε (POLE) mutations. Methods and results Forty-three ECs with POLE mutations were compared with a cohort of 202 ECs. Most POLE-mutated ECs were endometrioid [34/43 (79%]; the remaining tumours were mixed [6/43 (14%)], serous [2/43 (5%)], and clear cell [1/43 (2%)]. The endometrioid carcinomas were predominantly International Federation of Gynecology and Obstetrics grade 3 (27/43, 63%). The histotype dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 22 publications
9
49
0
Order By: Relevance
“…However, we can hypothesize that there may be a threshold of mutational burden that tumor cells can tolerate (38). There is also evidence that POLE ultramutated tumors are associated with peritumoral lymphocytes and tumor-infiltrating lymphocytes (28), which exhibit an enhanced T-cell antitumor response to antigenic neoepitope expression (39,40). This immune response may play a mechanistic role in the observed favorable prognosis, as an increased immune response in these tumors may decrease metastatic potential leading to a less-aggressive tumor (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we can hypothesize that there may be a threshold of mutational burden that tumor cells can tolerate (38). There is also evidence that POLE ultramutated tumors are associated with peritumoral lymphocytes and tumor-infiltrating lymphocytes (28), which exhibit an enhanced T-cell antitumor response to antigenic neoepitope expression (39,40). This immune response may play a mechanistic role in the observed favorable prognosis, as an increased immune response in these tumors may decrease metastatic potential leading to a less-aggressive tumor (28).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that POLE ultramutated tumors are associated with peritumoral lymphocytes and tumor-infiltrating lymphocytes (28), which exhibit an enhanced T-cell antitumor response to antigenic neoepitope expression (39,40). This immune response may play a mechanistic role in the observed favorable prognosis, as an increased immune response in these tumors may decrease metastatic potential leading to a less-aggressive tumor (28). An increase in tumor-infiltrating T cells has also been observed in microsatellite unstable endometrial and colorectal tumors, where the immune response may also contribute to antitumor effects and in the case of colorectal cancers, improved prognosis (39,41).…”
Section: Discussionmentioning
confidence: 99%
“…1 The resulting increased immunogenicity has a clear histologic correlate by means of conspicuous lymphocytic infiltrates seen in both MMR deficient 2 and POLE mutated 3 ECs. Moreover, in a case-control study by Bakhsh et al, 3 International Federation of Gynecology and Obstetrics grade 3 endometrioid histology was documented in 27 (63%) of 43 POLE mutated tumors, and overall histologic grade was significantly higher when compared with a 202 EC control group. Similarly, International Federation of Gynecology and Obstetrics grade 3 endometrioid histology is overrepresented among POLE mutated ECs in The Cancer Genome Atlas data.…”
Section: Positive Pd-l1 Expression Was Not Associated With Ec-specifimentioning
confidence: 96%
“…Recent studies incorporating molecular classification in high‐grade endometrial carcinomas have demonstrated that the greatest lack of agreement in histotype diagnosis lies within the ultramutated/POLE, hypermutated/MSI and copy‐number high/serous‐like categories . The first group, ultramutated/POLE, accounting for 8–10% of cases, has been characterized recently as showing endometrioid morphology with high‐grade or ambiguous features (Figure ) but very favourable clinical outcome . The second category, hypermutated/MSI, has been better characterized over many years; features described as Lynch syndrome‐related are ambiguous morphology and combinations of histotypes (including the presence of an undifferentiated component), isthmic location and lymphocytic infiltrates .…”
Section: Uterusmentioning
confidence: 99%